2008
DOI: 10.3174/ajnr.a1100
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Echo-Planar Diffusion-Weighted Imaging and Delayed Postcontrast T1-Weighted MR Imaging for the Detection of Residual Cholesteatoma

Abstract: BACKGROUND AND PURPOSE: Echo-planar diffusion-weighted imaging (DWI) and delayed postcontrast T1-weighted MR imaging (DPI) have been proposed in previous studies to detect residual middle ear cholesteatomas, with varying results. We assessed and compared these 2 techniques in patients with canal wall-up tympanoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
80
0
16

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(101 citation statements)
references
References 15 publications
(32 reference statements)
3
80
0
16
Order By: Relevance
“…Similarly, a certain cut-off value could not be indicated in our study as well. However, our findings are compatible with the literature data [3,16,18,[22][23][24].…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Similarly, a certain cut-off value could not be indicated in our study as well. However, our findings are compatible with the literature data [3,16,18,[22][23][24].…”
Section: Discussionsupporting
confidence: 80%
“…Delayed phase gadolinium enhanced T1 W imaging can be used for the diagnosis of cholesteatoma; however there are conflicting data about this method in the literature. Although some authors suggested that delayed phase post-contrast imaging is useful, others indicated that delayed phase post-contrast imaging could not provide additive information [9,16]. These conflicting results were believed to be related with the dimension of cholesteatoma [16].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The discrepancy between the sensitivity and the specificity is mainly caused by a large variation in the size of the residual cholesteatomas among the studies (Table 2). Indeed, the lowest size of the detected residual cholesteatoma ranged from 4 to 5 mm (1,15,20). In the present study, the lowest cholesteatoma size detected with HASTE DWI was 4 mm.…”
Section: Discussionmentioning
confidence: 66%
“…Duyarlılık ve özgüllük oranları; Aikele ve ark. nın [1] yaptıkları çalışmada sırasıyla %77 ve %100, Stasolla ve ark.nın [12] yaptıkları çalış-mada %86 ve %100, Jindal ve ark.nın [13] yaptıkları çalışmada %83 ve %82, Vercruysse ve ark.nın [14] yaptıkları çalışmada %12.5 ve %100, Venail ve ark.nın [15] yaptıkları çalışmada ise %60 ve %72 bulunmuştur. Bizim çalışmamızda ise EP-DAG'nin duyarlılık ve özgüllüğü sıra-sıyla %97.6 ve %92 bulundu.…”
Section: şEkil 3 Sol Kulakta Geçirilmiş Masteidektomi Ameliyatı öYküunclassified